Rhododendron suaveolens - Tsen, S.; Mohd Yusof, Nur Adillah, M.Y.; Khoo, E.; Khoo, E.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Rhododendron suaveolens is a small tree, endemic to Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 108 km2 and 6,590.8 km2, respectively. Although the AOO is calculated from known existing records, it is considered that the actual AOO may be considerably larger than this due to under sampling. Commonly found on western mountain ranges in Sabah, mostly within protected areas. Hence, assessed as Least Concern. Rhododendron suaveolens is endemic to Sabah, Malaysia.